Mediating effect of corporate sustainability on corporate governance and performance of banks in Ghana: a post banking crisis perspective - Sharon Donnir; Kingsley Tornyeva (Cogent Business & Management, 2024)
The aim of the study was to investigate the mediating effect of corporate sustainability on corporate governance and performance of banks in Ghana from the post banking crisis perspective. Adopting the purposive sampling technique, 302 key and senior management personnel from all the 23 banks constituted the study sample. The study explored primary data through the use of structured questionnaire to obtain data. In analyzing the data, Partial Least Square Structural Equation Modelling (PLS- SEM) was employed. The study revealed that, corporate governance has insignificant positive effect on bank performance; bank sustainability has significant positive effect on performance and sustainability mediates the corporate governance and bank performance nexus. The study has made significant contributions to both theoretical and empirical literature and has also advanced the on-going discourse on sustainability. Again, it will influence the development of further policies; reemphasizing the sectors' policies on corporate governance, sustainability performance and disclosures and influence related managerial decisions and strategies. The implication of the study from theoretical dimension, the study has extended literature on agency, stakeholder and signaling theories. For policy development and practice, the study will have significant implications on future policies as well as managerial decisions and strategies on corporate governance and sustainability in the banking sector.Corporate governance is consistently viewed as very crucial in the corporate world especially in the banking industry. Gradually, sustainability has not only emerged as a global concern, but the corporate world has embraced the concept with heighten recognition, advocacy and investment in corporate sustainability. In Ghana, the 2017 – 2018 banking sector crisis attracted several criticisms on the governance structures while stakeholders also raised several concerns on the sustainability of the sector after the crisis. Though, there have been some reforms in the sector to address these issues, it is not certain as to whether the corporate governance in the post crisis era influences performance and whether sustainability plays any significant role. This paper investigates the mediating effect of corporate sustainability on corporate governance and performance of banks in Ghana from the post banking crisis perspective and aims to provide empirical evidence to guide policy directions and operations in the Ghanaian banking sector.
Keywords: M49; 650; Collins Ntim; University of Southampton; United Kingdom of Great Britain and Northern Ireland